The Dynamics of Platelet Content in Patients with Diffuse Peritonitis as a Predictor of Disease Outcome - B. V. Sigua; P. A. Kotkov; S. V. Petrov; V. P. Zemlyanoy (Неотложная медицинская помощь)
BACKGROUND. Absolute numbers of platelets are of key importance for determining the severity of multiple organ failure in sepsis, while their fluctuations within normal values are not taken into account. At the same time, early detection of a downward trend in this parameter may have greater predictive value in predicting disease outcomes.   AIM OF STUDY. To identify trends in changes in platelet levels in patients with widespread peritonitis and determine the possible relationship of these changes with the outcome of the disease.   MATERIAL AND METHODS. The basis of the work was an analysis of the results of treatment of 220 patients with diffuse secondary peritonitis who were treated at the Elizavetinskaya Hospital in 2013–2019. A correlation analysis was conducted to identify relationships between disease outcomes, assessed according to the severity of postoperative complications, and the degree of platelet reduction, expressed in platelet ratio. The further ROC analysis allowed us to identify a threshold value of the platelet ratio, which excess indicated a high risk of an unfavorable outcome.   RESULTS. Based on the data obtained, the threshold value of the platelet ratio in the first two days has no clinical significance. At the same time, starting from the third 3rd day of the postoperative period, the quality of the resulting classifier increased, which confirms the prognostic significance of the threshold value of the platelet ratio, which was 1.72 on the third 3rd day after surgery. In other words, a decrease in platelet levels more than 1.72-fold on the 3rd day indicates a high risk of an unfavorable outcome, which may be associated primarily with intra-abdominal complications. This provision also indirectly confirms the fact that among patients with platelet ratio (PR) values exceeding 1.72 on the 3rd day, 68.7 % ultimately underwent repeated surgical interventions (33 patients out of 48 with high PR values, and the overall mortality rate was 72.1 %.Similar indicators in the subgroup with low PR values were 27.6 % of reoperated patients (29 of 105) and 26.7 % of unfavorable outcomes.   CONCLUSION. The results obtained indicate that the degree of platelet reduction, rather than their absolute levels, has greater predictive value in patients operated on for diffuse peritonitis.